Tin Sulphide Nanostructures Synthesized By Chemical Bath Deposition For Near-Infra-Red Photodetector Applications - Mahdi, Mohamed Saleh (2017)
This study aims to optimize the growth parameters for synthesizing nanostructured tin sulphide (SnS) thin films for efficient photodetector devices. A good crystal quality and low dark current are significant prerequisites in obtaining a high photodetector device performance. In addition, low temperature growth of thin film allows the use of polyethylene terephthalate (PET) material as a substrate. The growth of thin films was achieved using chemical bath deposition technique (CBD).